Peranan Pendidikan Olahraga dalam Meningkatkan Pembelajaran dan Pengembangan Mahasiswa melalui Aktivitas Fisik: Sebuah Kajian Literatur - Anindito, Filardi; Nabillah, Azry Ayu (Lentera: Jurnal Ilmiah Kependidikan, 2023)
This journal discusses the importance of physical education in enhancing learning and development among college students through physical activities. By using literature review and related studies, the authors explore the main benefits of physical education as well as its implementation and influence on the learning experience of students in the college environment. Physical education has been proven to provide many benefits for the physical health of students. Regular physical activity can help improve fitness and heart health, reduce the risk of obesity, improve bone health, and increase immune system function. In addition to physical health benefits, physical education also shows benefits in developing social skills and academic performance among students. In the context of social skills, sports can help students build leadership skills, teamwork, communication, and self-confidence. Students who are involved in sports activities also tend to have stronger social networks and more opportunities to build beneficial interpersonal relationships. Furthermore, research has shown that students who are involved in sports tend to perform better academically. Sports can help improve focus and concentration, enhance critical thinking skills, and improve problem-solving abilities. Additionally, sports activities can help reduce stress and increase mental well-being, which can improve motivation and academic performance. The journal also discusses strategies and approaches that can be used to integrate physical education into the college curriculum. Some of these strategies include expanding sports programs, providing access to adequate sports facilities, and enhancing support and motivation for students involved in sports activities. In conclusion, this journal shows that physical education provides many benefits for college students. By integrating physical education into the curriculum, colleges can help improve the physical health, social skills, and academic performance of their students.